Neonatal tooth in maxillary molar region: A case report - Avik Narayan Chatterjee; Raju Biswas; Sauvik Galui; Subrata Saha; Subir Sarkar (Wolters Kluwer Medknow Publications, 2020)
Those teeth that erupt within the first month of life are called neonatal teeth. It may occur in any region of the maxillary or mandibular arches but its incidence in the maxillary molar areas is extremely rare. A case of neonatal tooth in the maxillary molar region has been presented here.